OS MAMÍFEROS CORROBORAM O MARANHÃO COMO SENDO UM ESTADO ECÓTONO: COMPOSIÇÃO DAS ESPÉCIES DE MAMÍFEROS NÃO-VOADORES E SUAS ÁREAS PRIORITÁRIAS PARA CONSERVAÇÃO - VIEIRA, Odgley Quixaba. (2021)
Brazil is the most biodiverse country on Earth, with the Amazon and Cerrado biomes in particular having high levels of species richness. In the state of Maranão, located in the midnorth region of the country, lies an ecotonal zone between the Amazon, Caatinga, and Cerrado biomes. This results in the region having areas with high biodiversity and conservation priority. Despite this, the mammalian fauna of the region is still poorly known. We sampled the nonvolant mammals at several sites in Maranhão state. Small mammals were sampled using live traps, whereas medium and large-sized mammals were surveyed through transect sampling, interviews, and camera traps. We also searched literature extensively through trustable digital platforms. We recorded 89 nonvolant species for Maranhão state, of which 23 are threatened with extinction. The ecotonal nature of the region was supported by the number of species associated to each biome (65 species for the Cerrado and 65 in the Amazon), as well as by a principal component analysis, showing extensive overlap among species of each biome. Historical events such as expansion-retraction of rainforests in open landscapes as well as contemporary habitat loss, resulted in some of the species being detected outside their known distribution limits. Species distribution models showed that an area of 69,000 km2 within the state is of high conservation priority for threatened mammalian species. These areas are located in the buffer zones of existing protected areas such as the Gurupi region, Chapada das Mesas National Park, Mirador State Park, the middle Parnaíba river, and the Nascentes do Rio Parnaíba National Park. Ensuring the protection of the areas identified in this study, will improve the long-term conservation prospects of threatened species by allowing viable populations and habitat connectivity between existing protected areas.